SpoIIE mutants of Bacillus subtilis comprise two distinct phenotypic classes consistent with a dual functional role for the SpoIIE protein - Imrich Barák; Philip Youngman (1996)
Mutations in the spoIIE locus of Bacillus subtilis block sporulation at the stage of asymmetric septation and prevent compartment-specific activation of the transcription factor delta F. Recent ultrastructural studies of spoIIE mutants led to the conclusion that cells blocked at the stage of asymmetric septation form primarily thick septal structures similar to those formed at the mid-cell site during vegetative growth, although in an earlier study Piggot (J. Bacteriol. 114:1241-1253, 1973) clearly detected a more complex range of phenotypes. We have examined the phenotypes of six spoIIE mutants, including one example of the previously studied null type, spoIIE21. We confirmed that the spoIIE21 mutant and two other null mutants exhibit the classic thick-septum phenotype. However, two of the missense mutants, the spoIIE64 and spoIIE71 mutants, were found to display a strikingly different phenotype characterized by the presence of only thin asymmetric septa, frequently at both polar positions, as noted by Piggot. This phenotype is essentially identical to those of spoIIA (delta F) and spoIIG (delta E) null mutants, which also form sporulation septa that appear structurally normal at the level of electron microscopy. Despite the formation of apparently normal asymmetric septa, spoIIE64 and spoIIE71 mutants are fully defective in activation of delta F-dependent gene expression. These results indicate that the functional roles performed by SpoIIE in septum assembly and sigma factor regulation are distinct and separable.